Towards green filtration: Thyme-based antibacterial nanofiber media as alternatives to synthetic counterparts - Zahra Shafiei; Farideh Golbabei; Mohammad Reza Pourmand; Ensieh Masoorian; Mohammad Mehdi Shirmohammadi; Kamal Azam; Vida Shahbazian; Saba Kalantary (MethodsX, 2025)
This study presents a comparative strategy for incorporating natural and synthetic antibacterial agents into electrospun nanofiber media for face mask applications, addressing concerns over toxicity and environmental impact. Polyacrylonitrile (PAN) nanofibers containing thyme extract (5,20, 40, 60 wt %) and ZIF-8 (5,7, 10, 15 wt %) were fabricated and characterized. Morphological analysis confirmed uniform, bead-free nanofibers with diameters ranging from 207.5 to 234.2 nm and membrane thicknesses around 150 µm. FTIR and XRD results verified the successful integration and chemical interaction of additives with the PAN matrix. Filtration performance tests revealed that thyme-based nanofibers (40 wt %) achieved 96.83 % particle filtration efficiency (PFE) at 0.3 µm, 100 % bacterial filtration efficiency (BFE), and a low pressure drop of 20.33 Pa. ZIF-8 nanofibers (7 wt %) showed 96.58 % PFE and 96.06 % BFE with a slightly higher pressure drop (25 Pa). Time-kill assays indicated stronger antibacterial activity for thyme over ZIF-8 during a 4-hour period. Compared to commercial melt-blown filters, both types of nanofibers provided improved filtration with acceptable breathability. The results suggest that thyme-loaded nanofibers offer a safe, biodegradable alternative to synthetic agents like ZIF-8, though further studies on durability, scalability, and long-term performance are needed. • Thyme extract demonstrated superior antibacterial and filtration performance compared to ZIF-8. • Electrospun nanofibers significantly outperformed melt-blown media in filtration efficiency. • The study supports natural compounds as sustainable, non-toxic alternatives for face mask applications.